1985
DOI: 10.1007/bf00402722
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanine: High-dose 2-H infusions in goats

Abstract: 6-Thioguanine (6TG) is poorly absorbed after oral administration. Bolus injections of 6TG result in high peak concentrations with relatively short-lived plasma concentrations. In vitro studies have shown the importance of prolonged exposure to 6TG. Therefore we administered 6TG by infusion at a dose rate of 2 mg/h over 2 h. In three goats we determined the plasma concentration-time curves of 6TG and its riboside (6TGR). A steady state was reached for 6TG and was almost reached for 6TGR within the 2 h of infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The mean steady-state TG CSF concentration was 0.5 lM during CIVI, a concentration that is approximately tenfold higher than the in vitro IC 50 values in human lymphoblastic cell lines [2]. The CSF penetration of 18% observed in our study is similar to the estimated 25% penetration previously observed in an animal model [18]. The CSF penetration of TG is comparable to the CSF penetration of MP [3].…”
Section: Discussionsupporting
confidence: 78%
“…The mean steady-state TG CSF concentration was 0.5 lM during CIVI, a concentration that is approximately tenfold higher than the in vitro IC 50 values in human lymphoblastic cell lines [2]. The CSF penetration of 18% observed in our study is similar to the estimated 25% penetration previously observed in an animal model [18]. The CSF penetration of TG is comparable to the CSF penetration of MP [3].…”
Section: Discussionsupporting
confidence: 78%